1994
DOI: 10.1093/nar/22.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the mouse ribosomal protein S24 multigene family: a uniquely expressed intron-containing gene with cell-specific expression of three alternatively spliced mRNAs

Abstract: A family of 16 genes encoding the mouse ribosomal protein S24 was identified, and four members from this family were cloned. A single expressed intron-containing S24 gene (termed mrpS24) and one pseudogene (mrpS24p) were completely sequenced and characterized. The mrpS24 gene has seven exons and six introns spanning over 5.1 x 10(3) nucleotides (nt). The cap site of S24 was mapped to a G residue four nt upstream of a polypyrimidine tract and 15 nt downstream of a TATA-like (TATGA) element. The 5' region (-325 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 67 publications
1
10
1
Order By: Relevance
“…S09197) rp available from the literature. This difference may be explained by alternative splicing of S24 premRNA observed earlier by Ro and co-workers [38] who had sequenced the single expressed intron-containing S24 gene of mouse. They found that alternative splicing of the mini exons V and VI leads to different species of S24 mRNA.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…S09197) rp available from the literature. This difference may be explained by alternative splicing of S24 premRNA observed earlier by Ro and co-workers [38] who had sequenced the single expressed intron-containing S24 gene of mouse. They found that alternative splicing of the mini exons V and VI leads to different species of S24 mRNA.…”
Section: Discussionmentioning
confidence: 85%
“…Two forms of this mRNA, namely S24a mRNA and S24c mRNA, encode the same amino acid sequences which in the case of S24c have an extra tripeptide (PKE) at the C-terminal end. S24c mRNA represents the major form in undifferentiated and transformed cells, whereas the level of S24a mRNA is higher in differentiated cells [38]. Human [37] and rat [36] amino acid sequences of S24 were deduced from the nucleotide sequence of cDNAs which had been isolated from human fibrosarcoma or regenerating rat liver cDNA libraries.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, ribosomes would be heterogeneous for PS1D protein, most of them containing a PS1D long isoform. So far, only two rps have been shown to be encoded as two isoforms: human S 24, which is encoded by alternatively spliced mRNAs (25) and human S 4, which results from two transcribed genes, one on the X and a second on the Y chromosome (26). Whereas S 24 isoforms differ from each other only by the presence of three additional amino acids at the C terminus of the long isoform, S 4Y and S 4X differ at 19 of 263 positions.…”
Section: Discussionmentioning
confidence: 99%
“…As the His-tagged AEBP1 used in the enzyme assay was a recombinant protein expressed in and purified from bacteria, controls containing other His-tagged recombinant proteins (AEBP2 [20] and a ribosomal protein S 24 [21]), and controls containing bacterial extracts purified using similar procedures, were tested in the CP assay. These purified His-tagged recombinant proteins and purified bacterial extracts showed no CP activity, indicating that the CP activity observed in the AEBP1 assays was due to AEBP1 and not to other proteins co-purified in the purification procedure.…”
Section: Cp Activity Of Aebp1mentioning
confidence: 99%